1993
DOI: 10.7863/jum.1993.12.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of pressure gradients across iliac artery stenoses: duplex and catheter correlative study

Abstract: The present study investigates prospectively the validity and accuracy of the simplified Bernoulli equation in the duplex-derived determination of pressure gradients across iliac artery stenoses in patients with occlusive artery disease. In 28 patients (age range, 38 to 76 years; mean, 53 years) with short iliac artery stenoses, we obtained both duplex scan stenotic jet velocity and catheter pressure measurements. Mean and maximum pressure gradients were determined by both methods, as was the peak-to-peak cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…One noninvasive approach that has been suggested is to perform Doppler echocardiography using a simplified modification of the Bernoulli equation. 1,2 This method was, however, concluded not to yield reproducible or reliable results by Strauss et al 3 Another type of approach, which is still being investigated, is to combine microbubbles injected into the blood and diagnostic ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…One noninvasive approach that has been suggested is to perform Doppler echocardiography using a simplified modification of the Bernoulli equation. 1,2 This method was, however, concluded not to yield reproducible or reliable results by Strauss et al 3 Another type of approach, which is still being investigated, is to combine microbubbles injected into the blood and diagnostic ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, currently available non-invasive procedure using Doppler ultrasound has been reported to be non-reproducible. 22,23 The idea of using scattering properties of microbubbles for non-invasive pressure estimation has been around for over three decades. 13, 24 Fairbank and Scully 25 first proposed using air bubbles for cardiac pressure measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to quantify pressure loss from measured velocities using a modified Bernoulli equation with limited success. 42,43 The use of velocity ratios in multiple stenoses is somewhat controversial. While some reports have suggested that velocity ratios produce lower accuracy in the presence of severe adjacent disease, 44,45 others suggest that criteria are unaffected.…”
Section: Stenosis Criteriamentioning
confidence: 99%